How Do the Hospital Prices Paid by Medicare Advantage Plans and Commercial Plans Compare With Medicare Fee-for-Service Prices? - Jared Lane K. Maeda PhD, MPH; Lyle Nelson PhD (SAGE Publishing, 2018)
The prices that private insurers pay hospitals have received considerable attention in recent years, but most of that literature has focused on the commercially insured population. Although nearly one-third of Medicare beneficiaries are enrolled in a Medicare Advantage (MA) plan, little is known about the prices paid to hospitals by the private insurers that administer such plans. More information on the hospital prices paid by MA plans would provide additional insights into whether MA prices are more closely tied to Medicare fee-for-service (FFS) prices or commercial prices. Moreover, information on whether the hospital prices paid by MA plans vary with market characteristics or other factors would be useful for evaluating the performance of the MA program and analyzing proposals to modify it. In this study, we compared the hospital prices paid by MA plans and commercial plans with Medicare FFS prices using 2013 claims from the Health Care Cost Institute (HCCI) database. The HCCI claims were used to calculate hospital prices for private insurers, and Medicare's payment rules were used to estimate Medicare FFS prices. We focused on stays at acute care hospitals in metropolitan statistical areas (MSAs). We found MA prices to be roughly equal to Medicare FFS prices, on average, but commercial prices were 89% higher than FFS prices. In addition, commercial prices varied greatly across and within MSAs, but MA prices varied much less.